ISLAM WASATHIYAH SEBAGAI JALAN MODERASI BERAGAMA PERSPEKTIF AZYUMARDI AZRA - IZZA SAFITRI (ABDUSSALAM: Jurnal Pendidikan Dan Kebudayaan Islam, 2025)
This study aims to explore the thoughts of Prof. Dr. Azyumardi Azra regarding the concept of Islam wasathiyah as a path to religious moderation in Indonesia. The term wasathiyah comes from Arabic, meaning middle or intermediary, and is considered important for fostering peace in religious practices that often deviate from the original teachings of Islam. Azyumardi Azra emphasizes that the tradition of wasathiyah in Indonesia is the result of an inclusive and accommodative process of Islamization, supporting the strengthening of Islamic orthodoxy. This research employs a qualitative approach with a descriptive-analytical method, in which data is obtained from relevant literature reviews. The findings indicate that Azra's thoughts on wasathiyah encourage Muslims to adopt an inclusive attitude, appreciate differences, and uphold the values of moderation, which are essential for maintaining harmony in Indonesia's diverse society.